2016
DOI: 10.3390/ijerph13121231
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Adiposity Index and Lipid Accumulation Product Index: Two Alternate Body Indices to Identify Chronic Kidney Disease among the Rural Population in Northeast China

Abstract: We aimed to compare the relative strength of the association between anthropometric obesity indices and chronic kidney disease (CKD). Another objective was to examine whether the visceral adiposity index (VAI) and lipid accumulation product index (LAPI) can identify CKD in the rural population of China. There were 5168 males and 6024 females involved in this cross-sectional study, and 237 participants (2.12%) suffered from CKD. Obesity indices included body mass index (BMI), waist circumference (WC), waist-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
63
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 42 publications
6
63
1
2
Order By: Relevance
“…In a study conducted in a rural Chinese population, VAI was found to be a better predictor of CKD among women than BMI and WC. However, the same relationship was not found in men . In another study conducted in China, the VAI score was positively correlated with the albumin‐to‐creatinine ratio and was inversely related to eGFR .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In a study conducted in a rural Chinese population, VAI was found to be a better predictor of CKD among women than BMI and WC. However, the same relationship was not found in men . In another study conducted in China, the VAI score was positively correlated with the albumin‐to‐creatinine ratio and was inversely related to eGFR .…”
Section: Discussionmentioning
confidence: 82%
“…However, the same relationship was not found in men. 30 In another study conducted in China, the VAI score was positively correlated with the albumin-tocreatinine ratio and was inversely related to eGFR. 31 It is worth noting that impaired kidney function is associated not only with an increased risk of end-stage renal disease but also with a significantly higher risk of CVD.…”
Section: Discussionmentioning
confidence: 96%
“…The majority of previous studies reported VAI and LAP to be reliable indices in prediction of many metabolic disturbances …”
Section: Discussionmentioning
confidence: 99%
“…Even though a large number of studies in adult population indicate VAI and LAP as reliable markers of cardiometabolic risk advantageous over BMI and WC, there are another ones that report the opposite …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation